Recent Progress in the Understanding and Management of Acute Mountain Sickness: A Narrative Review - Gupta, Divyanshi; Wal, Pranay; Mishra, Mudita; Wal, Ankita; Rathore, Shruti; Shanker Pandey, Shiv; Saraswat, Nikita; Saxena, Bhagawati (Current Reviews in Clinical and Experimental Pharmacology, 2024)
Background: Individuals at higher altitudes may experience a decrease in blood oxygen levels, which can result in a variety of clinical illnesses, such as high-altitude pulmonary edema, high-altitude cerebral edema, and milder but more common acute mountain sickness (AMS). Objective: This study aims to review the current state of knowledge related to motion sickness, the risk of AMS, and pharmacological and non-pharmacological treatments for AMS. Methods: Several databases, including PubMed, Bentham Science, Elsevier, Springer, and Research Gate, were used to compile the data for the article following a thorough analysis of the various research findings connected to acute mountain sickness and motion sickness, along with treatments and prevention. Results: This article covers the research on mountain sickness as well as every imaginable form of conventional and alternative medicine. It contains ten medicinal plants that are useful in treating mountain sickness and various other remedies. Additionally, case studies are provided. Conclusion: Therefore, the information in the paper will help travel medicine specialists better personalize their appropriate care for patients who travel to high-altitude locations. Additionally, all available antiemetic medications, serotonin agonists, nonsteroidal anti-inflammatory drugs, and herbal treatments for motion sickness were discussed. The prevention and consequences of acute mountain sickness are also covered in this study.
Keywords: motion sickness